2013
DOI: 10.1088/0004-637x/765/1/69
|View full text |Cite
|
Sign up to set email alerts
|

Very Long Baseline Array Imaging of Parsec-Scale Radio Emissions in Nearby Radio-Quiet Narrow-Line Seyfert 1 Galaxies

Abstract: We conducted Very Long Baseline Array (VLBA) observations of seven nearby narrow-line Seyfert 1 (NLS1) galaxies at 1.7 GHz (λ18cm) with milli-arcsecond resolution. This is the first systematic very long baseline interferometry (VLBI) study focusing on the central parsec-scale regions of radio-quiet NLS1s. Five of the seven were detected at a brightness temperature of 5 × 10 6 K and contain radio cores with high brightness temperatures of > 6 × 10 7 K, indicating a nonthermal process driven by jet-producing cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 110 publications
(162 reference statements)
13
109
4
Order By: Relevance
“…This T B is only a lower limit to the peak value because our measurement includes some extended emission. The real core emission as detected with VLBI is smaller and Doi et al (2013) quote a peak value of T B > 7.7 × 10 7 K at 1.7 GHz. From the tapered image we measured a total flux density S ν,t = 18.85 ± 0.03 mJy (L tot = 1.03 × 10 40 erg s −1 ) and we obtained the flux density of the extended emission (S ν,e = 14.82 ± 0.1 mJy, L ext = 8.5 × 10 39 erg s −1 ), after subtracting the JVLA core flux density.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This T B is only a lower limit to the peak value because our measurement includes some extended emission. The real core emission as detected with VLBI is smaller and Doi et al (2013) quote a peak value of T B > 7.7 × 10 7 K at 1.7 GHz. From the tapered image we measured a total flux density S ν,t = 18.85 ± 0.03 mJy (L tot = 1.03 × 10 40 erg s −1 ) and we obtained the flux density of the extended emission (S ν,e = 14.82 ± 0.1 mJy, L ext = 8.5 × 10 39 erg s −1 ), after subtracting the JVLA core flux density.…”
Section: Resultsmentioning
confidence: 82%
“…However, no extended emission was found. Recently, Doi et al (2013) observed the galaxy nucleus with the Very Long Baseline Array (VLBA) looking for extended emission near the core of the AGN. The image only shows a compact core, but the flux density recovered by the authors at 1.7 GHz is only 4% of the NRAO VLA Sky Survey (NVSS) flux density at 1.4 GHz (S ν = 33.2 mJy; Condon et al 1998).…”
Section: Mrk 783mentioning
confidence: 99%
“…Doi et al (2012) found that the detection of extended emission is lower than expected from broad-line Seyferts and they suggest it could be due to the lower kinetic power of jets in low-mass AGNs, rather than the young age of the source. Interestingly, also the radio core of RQNLS1s and Seyferts display non-thermal characteristics, suggesting some link with jets (Giroletti & Panessa 2009, Doi et al 2013. Angelakis et al (in preparation) have studied the variability of four RLNLS1s detected at γ rays (J0324+3410, J0849+5108, J0948+0022, J1505+0326) at different radio frequencies.…”
Section: Radiomentioning
confidence: 99%
“…The combination of these radio/gammaray properties is reminiscent of blazars, which are characterized by Doppler-beaming on relativistic jets viewed from pole-on typically at parsec (pc) scales and by decelerated components at from kpc to Mpc scales. VLBI observations of the other several gamma-ray emitting NLS1s also indicate the presence of beamed jets at pc scales (D'Ammando et al 2012(D'Ammando et al , 2013bDoi et al 2011Doi et al , 2013Wajima et al 2014); some of them also show two-sided kpc-scale radio structures (Antón et al 2008;Doi et al 2011Doi et al , 2012. However, the radio jets are mildly relativistic and their powers are comparable to the least energetic blazars, on the basis of single-dish monitoring (Angelakis et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This situation suggests that jet powers may be intrinsically large sufficient to escape the core regions of host galaxies, but not so beamed because of relatively large viewing angles. For several nearby radio-quiet NLS1s, VLBI observations have also revealed pc-scale jet-like structures showing steep spectra, which are presumably generated through the same process as that of radio-loud NLS1s, but probably with an only difference in power or viewing angle for nonthermal jets (Giroletti et al 2005;Doi et al 2013Doi et al , 2015. Thus, at least a fraction of NLS1 nuclei has an ability to generate nonthermal jets, which have a wide range of radio powers; in some cases, the signatures of beaming effect on relativistic jets viewed from pole-on are observed.…”
Section: Introductionmentioning
confidence: 99%